Bovine Herpes Virus type 1 (BoHV-1) as a possible cause of encephalitis in cattle of the Colombian Magdalena Medio Region. Serological study and epidemiological analysis - Piedrahita, Luis E; Montoya, Luis M; Pedraza, Francisco J (My University, 2010)
The bovine Herpesvirus type 1 and type 5 (BoHV-1 and BoHV-5), causing diseases and significant economic losses in farms of worldwide. Both affect the nervous system of cattle, although BoHV-5 has been the most associated with this type of pathogenesis. Given the death of animals with nervous symptoms and negative diagnoses for rabies virus in the area of study, this research focused on the detection of positive reactors to bovine herpes virus serum neutralization. We collected 518 blood samples from animals without Herpesvirus vaccine, in the municipalities of Caparrapi, Cimitarra, Honda and Victoria, in the Middle Magdalena River Region. In addition, epidemiological information useful to discuss neurological disease was collected through primary and secondary sources. For the analysis of data was used chi-square test by identification of relationship between evidence of viral infection and the variables recorded. The results revealed that 286 cases were positive for Herpesvirus infection, corresponding to a prevalence of 55.5%, however, there was no statistical relationship (p < 0.05) between the presence of antibodies and the variables analyzed. In conclusion, some cases of neurological disease in cattle in this region could be due to infection with herpes viruses. We discussed about the presence of BoHV-1 and BoHV-5 in the ambient, diagnosis and monitoring plans, as well as economic losses, which may cause in herds in this area.
Herpes virus bovino tipo 1 (BoHV-1) como posible causa de encefalitis en bovinos de la región del magdalena medio colombiano. estudio serológico y análisis epidemiológico
Keywords: Bovine encephalitis; Serum neutralization; Virus herpes